2021
DOI: 10.1073/pnas.2026785118
|View full text |Cite
|
Sign up to set email alerts
|

One or two injections of MVA-vectored vaccine shields hACE2 transgenic mice from SARS-CoV-2 upper and lower respiratory tract infection

Abstract: Modified vaccinia virus Ankara (MVA) is a replication-restricted smallpox vaccine, and numerous clinical studies of recombinant MVAs (rMVAs) as vectors for prevention of other infectious diseases, including COVID-19, are in progress. Here, we characterize rMVAs expressing the S protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Modifications of full-length S individually or in combination included two proline substitutions, mutations of the furin recognition site, and deletion of the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 69 publications
(77 reference statements)
5
73
0
Order By: Relevance
“…Our prime-boost vaccinations with MVA--SARS-2-S did not impair the balanced T helper cell populations monitored in BALB/c mice by spectral flow cytometry. Of note, two additional studies also demonstrated the induction of predominantly TH1-type immune responses in mice immunized with MVA vector vaccines encoding SARS-CoV-2 S antigens (44,45). The importance of vaccine-induced T cell responses is illustrated by studies not only monitoring the adaptive immunity to SARS-CoV-2 in patients, but also demonstrating that strong SARS-CoV-2-specific CD4 + or CD8 + T cell responses are associated with low disease severity in individuals with COVID-19 (5).…”
Section: Microbiologymentioning
confidence: 97%
“…Our prime-boost vaccinations with MVA--SARS-2-S did not impair the balanced T helper cell populations monitored in BALB/c mice by spectral flow cytometry. Of note, two additional studies also demonstrated the induction of predominantly TH1-type immune responses in mice immunized with MVA vector vaccines encoding SARS-CoV-2 S antigens (44,45). The importance of vaccine-induced T cell responses is illustrated by studies not only monitoring the adaptive immunity to SARS-CoV-2 in patients, but also demonstrating that strong SARS-CoV-2-specific CD4 + or CD8 + T cell responses are associated with low disease severity in individuals with COVID-19 (5).…”
Section: Microbiologymentioning
confidence: 97%
“…Recent efforts have focused on using Modified Vaccina virus Ankara to develop vaccines against SARS-CoV-2. These have shown promising effects in mice and macaques [84][85][86][87]. With further research, it is expected that poxvirus vector-based vaccines will be licensed for humans, which requires substantially increasing the investments and efforts to understand the fundamental aspects of poxvirus replication, as well as collaboration among poxvirologists, immunologists, clinicians, and veterinarians.…”
Section: Employing Poxviruses To Fight Other Diseasesmentioning
confidence: 99%
“…Among them, the lungs of infected mice treated with chloroquine and bafilomycin A1 showed reduced infiltration of inflammatory cells and improved alveolar structure. Liu et al (2021) demonstrated that the recombinant modified vaccinia virus Ankaras (rMVAs) expressing modified forms of SARS-CoV-2 S proteins could not only suppress viral replication in the upper and lower respiratory tracts, but also reduce the expression of cytokines and chemokines in the lungs of hACE2 mice, suggesting that this vaccine had the potential to control COVID-19 during the current pandemic.…”
Section: Mousementioning
confidence: 99%